The Use of Antifactor Xa Assays in a Comprehensive Pediatric Extracorporeal Membrane Oxygenation Anticoagulation Protocol is Associated with Increased Survival and Significant Blood Product Cost-Savings - Sood, Shawn B.; Walker, Louisa Anne; Ramanujam, Rangaraj; Hardison, Daphne; Andrews, Jennifer; Smith, Andrew H.; Bridges, Brian C. (Journal of Pediatric Intensive Care, 2021)
We augmented our standard extracorporeal membrane oxygenation laboratory protocol to include antifactor Xa assays, thromboelastography, and antithrombin measurements. We performed a retrospective chart review to determine outcomes for patients placed on extracorporeal membrane oxygenation (ECMO) prior to and after the initiation of our anticoagulation laboratory protocol. A total of 663 consecutive ECMO runs were evaluated from January 1, 2007 to June 30, 2018. Of these patients, 252 were on ECMO prior to initiation of the anticoagulation laboratory protocol on September 1, 2011, and 411 patients were on ECMO after initiation of the protocol. There were no major changes to our extracorporeal membrane oxygenation circuit or changes to our transfusion threshold during this continuous study period. Transfusion utilization data revealed statistically significant decreases in almost all blood components, and a savings in blood component inflation-adjusted acquisition costs of 31% bringing total blood product cost-savings to $309,905 per year. In addition, there was an increase in survival to hospital discharge from 45 to 56% associated with the initiation of the protocol (p = 0.004). Our data indicate that implementation of a standardized ECMO anticoagulation protocol, which titrates unfractionated heparin infusions based on antifactor Xa assays, is associated with reduced blood product utilization, significant blood product cost savings, and increased patient survival. Future prospective evaluation is needed to establish an antifactor Xa assay-driven ECMO anticoagulation strategy as both clinically superior and cost-effective.
Keywords: antifactor Xa; antithrombin; extracorporeal membrane oxygenation; hemorrhagic; heparin